Clinical Hypnosis for Pediatric Gastrointestinal Disorders: A Practical Guide for Clinicians. Issue 3 (1st November 2022) - Chogle, Ashish; Lee, Amanda; Santucci, Neha R.; Yeh, Ann Ming; Prozialeck, Joshua D.; Borlack, Rachel E.; van Tilburg, Miranda A.L.
Abstract : Functional abdominal pain disorders (FAPDs) are common in the pediatric population and are associated with a significant reduction in quality of life. Bidirectional communication of the brain-gut axis plays an important role in pain generation and perception in FAPDs. There is a paucity of data on the best approach to treat this group of disorders, with no Food and Drug Administration (FDA)-approved drugs and scarce research to substantiate the use of most medications. Use of hypnosis in pediatric FAPDs is supported by evidence and has long-term benefits of up to at least 5 years beyond completion of treatment, highlighting the importance of incorporating this therapy into the care of these patients. The mechanisms by which clinical hypnosis is beneficial in the treatment of FAPDs is not completely understood, but there is growing evidence that it impacts functioning of the brain-gut axis, potentially through influence on central pain processing, visceral sensitivity, and motility. The lack of side effects or potential for significant harm and low cost makes it an attractive option compared to pharmacologic therapies. This review addresses current barriers to clinical hypnosis including misconceptions among patients and families, lack of trained clinicians, and questions around insurance reimbursement. The recent use of telemedicine and delivery of hypnosis via audio-visual modalities allow more patients to benefit from this treatment. As the evidence base for hypnosis grows, acceptance and training will likely increase as well. Further research is needed to understand how hypnosis works and to develop tools that predict who is most likely to respond to hypnosis. Studies on cost-effectiveness in comparing hypnosis to other therapies for FAPDs will increase evidence for appropriate healthcare utilization. Because hypnosis has applications beyond pain and is child-friendly with minimal to no risk, hypnosis could be an important therapeutic tool in the wider pediatric gastrointestinal population.